CXCR4–CXCL12–CXCR7, TLR2–TLR4, and PD-1/PD-L1 in colorectal cancer liver metastases from neoadjuvant-treated patients. (1st December 2016) - D'Alterio, Crescenzo; Nasti, Guglielmo; Polimeno, Marianeve; Ottaiano, Alessandro; Conson, Manuel; Circelli, Luisa; Botti, Giovanni; Scognamiglio, Giosuè; Santagata, Sara; De Divitiis, Chiara; Nappi, Anna; Napolitano, Maria; et al.
ABSTRACT: A neoadjuvant clinical trial was previously conducted in patients with resectable colorectal cancer liver metastases (CRLM). At a median follow up of 28 months, 20/33 patients were dead of disease, 8 were alive with disease and 5 were alive with no evidence of disease. To shed further insight into biological features accounting for different outcomes, the expression of CXCR4–CXCL12–CXCR7, TLR2–TLR4, and the programmed death receptor-1 (PD-1)/programmed death-1 ligand (PD-L1) was evaluated in excised liver metastases. Expression profiles were assessed through qPCR in metastatic and unaffected liver tissue of 33 CRLM neoadjuvant-treated patients. CXCR4 and CXCR7, TLR2/TLR4, and PD-1/PD-L1 mRNA were significantly overexpressed in metastatic compared to unaffected liver tissues. CXCR4 protein was negative/low in 10/31, and high in 21/31, CXCR7 was negative/low in 16/31 and high in 15/31, CXCL12 was negative/low in 14/31 and high in 17/31 CRLM. PD-1 was negative in 19/30 and positive in 11/30, PD-L1 was negative/low in 24/30 and high in 6/30 CRLM. Stromal PD-L1 expression, affected the progression-free survival (PFS) in the CRLM population. Patients overexpressing CXCR4 experienced a worse PFS and cancer specific survival (CSS) ( p = 0.001 and p = 0.0008); in these patients, KRAS mutation identified a subgroup with a significantly worse CSS ( p < 0.01). Thus, CXCR4 and PD-L1 expression discriminate patients with the worse PFS within the CRLM evaluated patients. Within the CXCR4 high expressing patients carrying Mut-KRAS in CRLM identifies the worst prognostic group. Thus, CXCR4 targeting plus anti-PD-1 therapy should be explored to improve the prognosis of Mut-KRAS-high CXCR4-CRLMs.